A Study on the Readiness and Feasibility of Implementing E-HRM in the SMEs in Malaysia - Lai Wan, Hooi; Selamat, Ruzita (Universiti Teknologi Malaysia, 2006)

(untitled)
his study attempts to understand the extent of e-HRM practised in the small and medium sized enterprises (SMEs) in the manufacturing sector in five main areas of human capital management, which is believed to have a significant impact on the competitiveness of the industry, namely, recruitment, compensation and benefits, training and development, communication and performance appraisal. The piece will also focus on the fact that the readiness and feasibility of implementing e-HRM in the SMEs in Malaysia is dependent on the availability of resources and the attitude of the employees. The resources covered in this study include expertise, financial and technical resources.